Agency, productivity and sustainability: cocoa production experience in the hamlet of El Tesoro on Barinas state 2017-2018 (Mayéutica Revista Científica de Humanidades y Artes, 2019)
The cultivation of cocoa refers to a vast trajectory in the agriculture of Venezuela, from which numerous social actors have promoted various actions of scientific interest, hence, this research sought to approach, understand the social processes generated by the agroecological and sustainable experience in the cultivation of cocoa in the hamlet of El Tesoro in Barinas state, valuing the dynamics among the producers as expressions of collective agency and as a coadjutant element in the preservation of the productivity and sustainability of the area. Included in the theoretical line of this research are statements by Hernández and Escala (2011), Altieri and Nicholls, (2012) and discussions outlined in the Human Development Report of 1996 of United Nations Development Programme. This is a qualitative research, with the techniques of ethnographic interviews, indepth interviews and observations. The process of interpretation and analysis of the information was developed under a system of categorization that allowed the construction of comprehensive conclusions of the social reality studied. Among the findings, there are, the promotion of agency processes through the cocoa activity, characterized by the creation of spaces for improvement of the social, economic and environmental area of the parties involved. Cocoa emerges as a tool for social transformation that generates opportunities for the achievement of individual and collective wellbeing, making it a resource highly valued by producers in the area.
Keywords: Collective Agency; Agroecological Practices; Sustainability; Human Development; Cocoa